Anaerobic Digestion of Fruit Waste Mixed With Sewage Sludge Digestate Biochar: Influence on Biomethane Production - Ambaye, Teklit Gebregiorgis; Rene, Eldon R.; Dupont, Capucine; Wongrod, Suchanya; van Hullebusch, Eric D. (Frontiers in Energy Research, 2020)
The main aim of this study was to evaluate the biomethane potential (BMP) of fruit waste by incorporating additives such as sewage sludge biochar at different inoculum to substrate ratios (ISR) of 2, 1.5 and 1 (w/w). The results showed an improvement in the maximum methane production by 13, 20 and 27 % upon the addition of sewage sludge biochar produced at 350 C for ISR of 2, 1.5 and 1 (w/w), respectively, and an increase 12, 18 and 22% for the added biochar produced at 550 C for ISR of 2, 1.5 and 1 (w/w), respectively, compared to the BMP tests performed without the addition of biochar. In addition to this, the amount of biochar with the best effectiveness at ISR = 2, 1.5, and 1 was reported to be 0.5, 1, and 0.5 g / g VS-fruit waste of biochar produced at 350 C and 1.5, 1.5 and 1 g / VS-fruit waste for the sewage sludge biochar produced at 550 C, respectively. Finally, the highest methane production rates were registered for ISR = 2, 1.5, and 1 at 1, 1.5, and 1 g biochar produced at 350 C per g VS-fruit waste and 1.5, 0.5 and 1 g biochar produced at 550 C per g / VS-fruit waste, respectively. The results from this study showed that the effectiveness of the anaerobic digestion process depends on the ISR, biochar dose as well as the pyrolysis temperature used for the production of the sewage sludge digestate biochar.